Expert consensus on dynamics of laboratory tests for diagnosis of macrophage activation syndrome complicating systemic juvenile idiopathic arthritis. Issue 1 (19th January 2016) - Ravelli, Angelo; Minoia, Francesca; Davì, Sergio; Horne, AnnaCarin; Bovis, Francesca; Pistorio, Angela; Aricò, Maurizio; Avcin, Tadej; Behrens, Edward M; De Benedetti, Fabrizio; Filipovic, Alexandra; Grom, Alexei A; et al.
Abstract : Objective: To identify which laboratory tests that change over time are most valuable for the timely diagnosis of macrophage activation syndrome (MAS) complicating systemic juvenile idiopathic arthritis (sJIA). Methods: A multistep process, based on a combination of expert consensus and analysis of real patient data, was conducted. A panel of experts was first asked to evaluate 115 profiles of patients with MAS, which included the values of laboratory tests at the pre-MAS visit and at MAS onset, and the change in values between the two time points. The experts were asked to choose the 5 laboratory tests in which change was most important for the diagnosis of MAS and to rank the 5 selected tests in order of importance. The relevance of change in laboratory parameters was further discussed and ranked by the same experts at a consensus conference. Results: Platelet count was the most frequently selected test, followed by ferritin level, aspartate aminotransferase (AST), white cell count, neutrophil count, and fibrinogen and erythrocyte sedimentation rate. Ferritin was most frequently assigned the highest score. At the end of the process, platelet count, ferritin level and AST were the laboratory tests in which the experts found change over time to be most important. Conclusions: We identified the laboratory tests in which change over time is most valuable for the early diagnosis of MAS in sJIA. The dynamics of laboratory values during the course of MAS should be further scrutinised in a prospective study in order to establish the optimal cut-off values for their variation.